PERILAKU PENGGUNAAN INTERNET PADA REMAJA DESA AENG PANAS KECAMATAN PRAGAAN KABUPATEN SUMENEP - Ahmad Zulfikar Ali; Mohammad Yasin (Bayan lin-Naas : Jurnal Dakwah Islam, 2020)
Increasingly sophisticated technological developments affect human attitudes and behavior in carrying out their daily lives. This influence can be seen by the widespread use of the internet both among adults and adolescents. This is not surprising if you see the various functions and benefits that can be obtained through the use of the internet. This can be seen when assessing the internet from the positive side only. However, like the media in general, if viewed from a negative side, some things that are not good for society will be found. Teenagers are one of the many groups of people who use the internet in their daily lives, teenagers who tend to be active and always filled with great curiosity encourage them to continue to cultivate their existence in facing the current digital era. With this unique typology of teenage characters, this research was conducted to find out how teenagers behave in using the internet and how the impact of internet use on teenagers is.From the results of the study it was found that the internet has become a daily need for teenagers with a duration of internet use between 1 to 12 hours. The internet is used to find information, add insight, and communicate with each other.The impacts arising from internet use on adolescents tend to be negative with several field generations in the form of; often forget the time, lazy to study, lack of socializing, calls parents behind, busy being alone, and more concerned with himself when together.